PINK1 drives Parkin self-association and HECT-like E3 activity upstream of mitochondrial binding - Lazarou, Michael (The Rockefeller University Press, 2013)
PINK1 activates the HECT-like E3 ubiquitin ligase activity and self-association of Parkin upstream of its translocation to mitochondria and induction of mitophagy.